Achieving the Sustainable Development Goal on Poverty Eradication - Alain de Janvry; Elisabeth Sadoulet (Fondation pour les études et recherches sur le développement international (FERDI), 2017)
Achieving the Sustainable Development Goal on poverty eradication requires focusing on agriculture and rural areas. Increasing technology adoption in staple food agriculture—the Green Revolution—will however not suffice. Key is to manage an agricultural and a rural transformation whereby farming systems become more diversified and a rural non-farm economy emerges to complement agricultural sources of income and smooth labor calendars for the rural labor force.
Keywords: 330; SDG; Sustainable development goals